2008
DOI: 10.1055/s-2008-1078764
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Arterial Thrombosis at Birth: Case Report and Literature Review

Abstract: Neonatal thromboembolism is rare and in most cases iatrogenic from indwelling central catheters, peripheral arterial lines, and umbilical lines. It often requires urgent intervention to restore perfusion and to avoid morbidity and even mortality. Very few case reports of neonatal arterial thrombosis at birth are described in the literature. We present the case of a full-term infant noted to have marked left arm swelling at birth. Doppler ultrasound of the arm demonstrated a large thrombus in the left subclavia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 39 publications
0
47
0
Order By: Relevance
“…327 Tarry et al 328 identifi ed 44 cases of peripheral arterial TEs secondary to catheterizations or arterial punctures in children with nephrotic syndrome. Friedman et al 309 reported the use of microvascular surgery in a heterogeneous group of neonates with vascular injury.…”
Section: Therapy For Peripheral Artery Thrombosis Secondary To Periphmentioning
confidence: 99%
“…327 Tarry et al 328 identifi ed 44 cases of peripheral arterial TEs secondary to catheterizations or arterial punctures in children with nephrotic syndrome. Friedman et al 309 reported the use of microvascular surgery in a heterogeneous group of neonates with vascular injury.…”
Section: Therapy For Peripheral Artery Thrombosis Secondary To Periphmentioning
confidence: 99%
“…The prevalence of symptomatic neonatal arterial thrombosis is approximately 1 in 40,000 births, with 90% of cases linked to indwelling intra-arterial catheters (1)(2)(3). Other risk factors are sepsis, polycythemia, maternal diabetes, asphyxia, and inherited thrombophilias (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Other risk factors are sepsis, polycythemia, maternal diabetes, asphyxia, and inherited thrombophilias (1)(2)(3). Neonate presenting with isolated pulmonary artery thrombosis with severe pulmonary arterial hypertension is a rare event (4).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation varies depending on the extremity involved and the initial timing of thrombosis [1,2]. Several case reports on extremity hypoperfusion and gangrene due to intrauterine thrombosis at birth can be found in the literature [1,2,3,4,5,6,7,8,9,10]. Although the condition is usually associated with a poor prognosis, favorable outcomes have also been reported [3,4] (table 1).…”
Section: Introductionmentioning
confidence: 99%